The relationship between Rheumatoid Arthritis and the intestinal microbiota: A literature review (Research, Society and Development, 2024)
This literature review aims to discuss in detail the possible connection between the pathogenesis of Rheumatoid Arthritis and intestinal dysbiosis. Rheumatoid Arthritis is an autoimmune condition that affects the joints, generating inflammation and chronic pain, as well as having extra-articular repercussions. Lately, there has been a growing interest in the role of the intestinal microbiota in the origin and evolution of these diseases. In this study, we analyzed a compilation of scientific articles that investigate the composition of this microbiome in patients with Rheumatoid Arthritis, in addition to also investigating the mechanisms by which the microbiota can influence the immune response and the pathogenesis of Arthritis. The results highlight the complexity of this interaction, indicating that changes in the microbiome may play a crucial role in the emergence and progression of Rheumatoid Arthritis.